Tree diversity and conservation in logged rainforest - Sheil, Douglas; Sayer, Jeffrey A.; O'Brien, T. (1999)
C. H. Cannon et al. report an increase in tree diversity 8 years after selective logging in Borneo. These results accord with theoretical expectations and with previous observations; however, the significance of these findings is debatable. Cannon et al.'s analyses are confounded by differences in stem counts per sample and although Cannon et al. note the value of rarefaction as an alternative approach they do not provide the appropriate evaluations. Thus, the finding of a general increase in stem-diversity remains unsubstantiated. A greater concern arises from the assertion by Cannon et al. that such diversity patterns have some previously unrecognised conservation significance. Species are not equivalent, and species counts do not represent any inherent conservation value or provide a measure of ecological integrity. It is no paradox that habitat deterioration may be marked by a transient rise in stem diversity. Selective logging is a relatively nonselective agent of short-term tree mortality. Stems from all the species that are present before logging will usually persist at reduced densities after harvesting is completed. In addition, logging increases the heterogenity of forest microhabitats and provides considerable space for colonisation by immigrant species. These additions are predominantly good dispersers and "disturbance dependent" species rather than the more vulnerable and restricted taxa which characterise old-growth vegetation. Short periods tell us little about the long-term maintenance of species in managed systems where some stems have the potential to live for centuries. While production forests have numerous conservation values any benefits from post-logging increases in tree diversity remain doubtful.